Odour, perfume, and the female body in ancient Rome - Lawrence, Thea (2019)
This thesis examines the representation of the scented female body in the literary culture of late Republican and early Imperial Rome. Recent years have seen increasing scholarly interest in odour and olfaction in antiquity, building on anthropological and sociological research on the cultural relativism of olfactory perception and its associations and interpretations. Through its connections to sexuality, bodily fluids, and corporeal corruption, odour provides a fascinating lens through which to scrutinise the ancient female body.